What Do Indonesian Think About Waqf? A Sentiment Analysis Using Machine Learning (UIN Sunan Kudus, 2023)
This study aims to identify the most popular topics and words in conversations on Twitter with the topic of waqf in Indonesia. This study also aims to identify the sentiments and emotions of netizens about waqf in Indonesia. This study uses a qualitative method with a sentiment analysis approach with the help of Orange Data Mining. The data used are tweets from Twitter taken from April 10, 2023, to April 24, 2023. Researchers used the keyword